If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=2*3/4*3/4-3*3/4+1
We simplify the equation to the form, which is simple to understand
y=2*3/4*3/4-3*3/4+1
Simplifying:
y=+6/4*3/4-3*3/4+1
Simplifying:
y=+6/12/4-3*3/4+1
Simplifying:
y=+6/12/4-9/4+1
Simplifying:
y=0.5/4-9/4+1
Simplifying:
y=0.125-9/4+1
Simplifying:
y=0.125-2.25+1
We move all terms containing y to the left and all other terms to the right.
+1y=0.125-2.25+1
We simplify left and right side of the equation.
+1y=-1.125
We divide both sides of the equation by 1 to get y.
y=-1.125
| (x-8)(x^2+8x+1)= | | 14a=16(a+12) | | 6x^2+y^2-x^2+5+x-3y^2= | | -4x^2+6x-3=0 | | (x-1)(x^2+x-8)= | | x+(x-51)=699 | | 8(x^2+9)(x+8)= | | 150=4t-160 | | x+(x-58)=842 | | 4000=216+N | | (x-2)(x^2+x+4)= | | 4x+2x-10=21 | | 15x-3=30x+6 | | 3y+7=-6-56 | | (x-2)(x^2+4x+8)= | | (n+4)2-n=27 | | 58-x=842 | | x+6(-4)=25 | | x-58=842 | | 8x^3+72x^2+8x+72= | | X^2+14x-69=0 | | 2x+6=1-3c | | 9+y-(-x)-5-8y-4= | | 5-6x=2x+21 | | X^2+14x-16=53 | | S^2+14s-16=53 | | 6t-t=4 | | 2x+68=768 | | Y=3x^2-7 | | 3=4t+7 | | 2(1+6x)=-18+7x | | x+16+30x=93 |